PENGARUH ASIMETRI INFORMASI DAN MANAJEMEN LABATERHADAP BIAYA MODAL EKUITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2013-2015 - Putra, Yudi Partama (JURNAL EKOMBIS REVIEW, 2018)
Yudi Partama Putra; This study aims to (1) determine the effect of asymmetry of information on costs of equity at manufacturing companies listed in Indonesia Stock Exchange period 2013-2015, (2) know the effect of earnings management on equity capital costs at manufacturing companies listed on the Stock Exchange in 2013- 2015, (3) determine the effect of information asymmetry and earnings management simultaneously on the cost of equity capital in manufacturing companies listed on the Indonesian Stock Exchange 2013-2015. The population in this study is manufacturing company listed on the Indonesia Stock Exchange. While the sample selection is taken by using purposive sampling method. The classical assumption test used in this research is using normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. Analysis of data used to test the hypothesis is multiple linear regression analysis techniques. Based on the results of the research indicate that (1) information asymmetry has positive and significant effect to cost of equity (2) earnings management has no significant effect on Cost of equity. F test results show that the variable information asymmetry and earnings management simultaneously affect the cost of equity capital. The result of determination coefficient test with R square shows that variable information asymmetry and earnings management influence cost equity capital equal 10,7%, while the rest 89,3% influenced by other variables.Key Words: Information Asymetry, Earnings Management, and Cost Of Equity.